Two Paths, One Purpose? A Comparative Historical Study of Islamic Higher Education Development in Indonesia and Turkey - Khairuddin; Mahdi Handayani Sidik (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This research discusses the development of Islamic higher education in Indonesia and Turkey through a comparative historical approach, focusing on the social, political and cultural dynamics that influenced it. The main issue raised is how the two countries, despite having strong Islamic education traditions, adopted different paths in developing Islamic higher education systems. The aim of this study is to explore the differences and similarities in the development of Islamic higher education in the two countries and their impact on educational identity and curriculum integration. The method used is a historical comparative study with document analysis and primary sources related to the development of Islamic higher education in Indonesia and Turkey. The results show that although both countries face similar challenges in modernization, Indonesia maintains more religious identity in Islamic education, while Turkey leads to secularization by integrating Islamic higher education within the framework of secular education. The impact of these findings suggests that Islamic higher education in Indonesia and Turkey can teach each other lessons in integrating religious values with the demands of modern science, taking into account their respective social and political contexts.